2020
DOI: 10.1364/oe.402311
|View full text |Cite
|
Sign up to set email alerts
|

7X multiplexed, optofluidic detection of nucleic acids for antibiotic-resistance bacterial screening

Abstract: Rapid and accurate diagnosis of bacterial infections resistant to multiple antibiotics requires development of new bio-sensors for differentiated detection of multiple targets. This work demonstrates 7x multiplexed detection for antibiotic-resistance bacterial screening on an optofluidic platform. We utilize spectrally multiplexed multi-spot excitation for simultaneous detection of nucleic acid strands corresponding to bacterial targets and resistance genes. This is enabled by multi-mode interference (MMI) wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…To further improve multiplexing capabilities, Meena et al. (2020) designed a multi‐mode interference (MMI) waveguides optofluidic platform (Figure 7) to fabricate a seven‐plex antibiotic‐resistance bacterial screening method . The MMI waveguides can support multiple modes propagating with different propagation constants, which interfered with each other to produce distinguished spots at specific distances.…”
Section: Strategies and Applications Of Mobas In Food Safety Analysismentioning
confidence: 99%
“…To further improve multiplexing capabilities, Meena et al. (2020) designed a multi‐mode interference (MMI) waveguides optofluidic platform (Figure 7) to fabricate a seven‐plex antibiotic‐resistance bacterial screening method . The MMI waveguides can support multiple modes propagating with different propagation constants, which interfered with each other to produce distinguished spots at specific distances.…”
Section: Strategies and Applications Of Mobas In Food Safety Analysismentioning
confidence: 99%
“…The markers fluoresce in this light, and the fluorescence can be detected and measured by a photodetector as a signal for target presence. Targets detectable by this biosensor platform include antigens, cancer biomarkers, liposomes, nucleic acids, proteins, ribosomes, and virions [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this biosensor platform has been used to detect the H1N1 virus [7], various antibiotic-resistant bacterial genes [5], and the recent SARS-CoV-2 virus [1]. Meena et al demonstrated the detection of E. coli, E. aerogenes, K. pneumonia, KPC, and VIM with accuracies of 91.6%, 90.2%, 85%, 90%, and 90%, respectively; their tests yielded an average signal-to-noise ratio (SNR) of 39.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target multiplexing was implemented by exciting different targets with spectrally and/or spatially varying multispot light patterns generated by multimode interference (MMI) waveguides (29). When these were intersected with single or multiple analyte waveguide channels, the target fluorescence signal reflects the different spatial excitation patterns and up to 7× multiplexing has been demonstrated (30)(31)(32)(33)(34)(35). Critically, the flow-based detection on the waveguide chip is target agnostic and has enabled detection of a wide variety of biomolecules including liposomes, virions, nucleic acids, ribosomes, and proteins.…”
mentioning
confidence: 99%